Imperial College London’s saRNA Vaccine - COVAC1 - Pollock, Katrina (Henry Stewart Talks, 2020)
The self-amplifying RNA vaccine technology, Current stage of the clinical trial, Next steps in the clinical trial, The future of the vaccine